Exploring the Influence of Digital Transformation on Human Capital Development: Evidence from Small and Medium Enterprises in Indonesia - Meindro Waskito; Ali Mustafiq (Indonesian Journal of Business Analytics, 2025)
This study explores the causal and conditional influence of Digital Transformation (DT) on Human Capital Development (HCD) within Indonesian Small and Medium Enterprises (SMEs). A quantitative, cross-sectional survey was conducted among 405 SME managers across Indonesia’s trade, manufacturing, and service sectors. Using Structural Equation Modeling (SEM) with AMOS, the study tested five hypotheses linking digital strategy alignment (DSA), digital infrastructure investment (DII), and digital culture and flexibility (DCF) to two dimensions of HCD—digital skills (DS) and specialized digital knowledge (SDK)—while incorporating resource scarcity (RS) as a structural constraint and DS as a moderator. The results reveal that strategic alignment (DSA) exerts the strongest influence on specialized digital knowledge (SDK) (β=0.45, p<0.001), confirming that only strategically guided digitalization fosters advanced human capital formation. For SME managers, the study underscores that strategic digital alignment and continuous skill upgrading must precede technological investment to ensure sustainable transformation and competitiveness. This research advances the Resource-Based View (RBV) by empirically modeling human capital as a dynamic capability within digital transformation processes, offering rare quantitative evidence from an emerging economy context. It also introduces resource scarcity as a conditioning mechanism, enriching theoretical frameworks of digital maturity for developing countries.